2006
DOI: 10.2165/00019053-200624080-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Analyses of Azathioprine, Methotrexate and Prospective Pharmacogenetic Testing for the Management of Inflammatory Bowel Disease

Abstract: Our model suggests that both MTX and AZA may generate significant net cost savings and benefits for patients with IBD in New Zealand, with AZA likely to be more cost effective than MTX. Prospective testing for poor metabolisers of AZA may also be cost effective, with phenotype testing likely to be more cost effective than genotype testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 40 publications
0
65
0
Order By: Relevance
“…This indicates that TPMT metabolizer status is a useful adjunct to (but not replacement for) regular blood count monitoring. The clinical usefulness of prospective determination of TPMT metabolizer status is supported by pharmacoeconomic studies (Marra et al, 2002;Oh et al, 2004;Winter et al, 2004;Dubinsky et al, 2005;Priest et al, 2005).…”
Section: Thiopurine Methyltransferasementioning
confidence: 99%
“…This indicates that TPMT metabolizer status is a useful adjunct to (but not replacement for) regular blood count monitoring. The clinical usefulness of prospective determination of TPMT metabolizer status is supported by pharmacoeconomic studies (Marra et al, 2002;Oh et al, 2004;Winter et al, 2004;Dubinsky et al, 2005;Priest et al, 2005).…”
Section: Thiopurine Methyltransferasementioning
confidence: 99%
“…However, as many patients are refractory to current classes of therapeutics there is a need to develop novel antiinflammatory drugs with relevance to enterocolitis (Priest et al, 2006). Zebrafish models have been successfully used to identify small molecules with therapeutic application, including oncogene suppression and hematopoietic stem cell expansion (North et al, 2007;Yeh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although .70% of myelosuppression related to azathioprine use is not associated with TPMT polymorphism [13,18,19], screening as few as 20 patients for TPMT deficiency can prevent one adverse event over 6 months of therapy [20]. Furthermore, pharmacoeconomic models and prospective studies have demonstrated that genotype or phenotype screening for TPMT polymorphisms is cost-effective in patients with rheumatological disorders [20], inflammatory bowel disease [21,22], paediatric leukaemia [23] and autoimmune skin disease [24]. Other small prospective screening studies of TPMT activity have not adequately predicted toxicity in patients with inflammatory bowel disease [25,26].…”
Section: Discussionmentioning
confidence: 99%